Pengaruh Good Governance dan Kompetensi Aparatur Negara Terhadap Pencegahan Fraud dengan Whistleblowing System sebagai Variabel Moderating di Pemerintah Kota Binjai - Kinsky, Karina (Worksheet : Jurnal Akuntansi, 2025)
Fraud is one of the most important issue in Binjai City Government. Failures in e-government implementation and the whistleblowing system, along with incompetence among state apparatus, have created opportunities for fraud. The study uses a quantitative associative approach and analyzes data with Partial Least Square-Structural Equation Modeling (PLS-SEM) through SmartPLS software. The results show that Good Governance and State Apparatus Competence have a significant positive effect on Fraud Prevention. Additionally, the Whistleblowing System strengthens these relationships and serves as an important moderating control. This implies that improving governance and competence must be accompanied by an effective whistleblowing system. Therefore, Binjai City Government should focus on enhancing governance, competence, and the whistleblowing system to create a more transparent and accountable environment.